Structural changes of the cervical muscles in elder women with cervicogenic headache - Sureeporn Uthaikhup (2018)
© 2017 Elsevier Ltd Background Evidence suggests that cervicogenic headache is associated with increasing age. Cervical musculoskeletal impairments are common features in individuals with cervicogenic headache. There is some suggestion that the structure (size and fatty infiltration) of neck muscle may factor in or contribute to these impairments. Objective To investigate relative cross sectional areas (rCSAs) and fatty infiltrate in the cervical muscles in elders with cervicogenic headache compared to controls. Methods Fourteen elder women with cervicogenic headache and 14 controls participated in the study. The rCSAs and fat infiltration were measured for the rectus capitis posterior major, rectus capitis posterior minor, multifidus, semispinalis capitis, splenius capitis, longus capitis/colli, and sternocleidomastoid. Results Elder women with cervicogenic headache had significantly reduced rCSAs of the rectus capitis posterior major and multifidus muscles compared to controls (p  <  0.05). Larger amounts of fat infiltrates were also observed in the rectus capitis posterior major and minor and splenius capitis muscles in the cervicogenic headache group (p  <  0.05). There were no changes in the size and fat infiltrate in the cervical flexor muscles (p  >  0.05). Conclusion The study demonstrated muscle atrophy with increased fatty infiltration in regionally select muscles of the upper and segmental cervical spine in older women with cervicogenic headache. While such changes and their influence on clinical symptoms are unknown, they may have management implications. Future research investigations are required to determine whether such alterations could be modified with specific exercise and modifications to daily living to positively influence clinical symptoms.